Implementasi Sistem Informasi Pelayanan Administrasi Kependudukan Berbasis Web - Joko Dwi Mulyanto; Supriatiningsih Supriatiningsih (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2022)
Village government is one of the government agencies in charge of regulating and managing resources at the village level. One of the obligations of the village is to carry out population administration as a form of service to the community. The Kober Village Office, in providing population administration services, still does not use an automated system so that the administrative service process and population data processing becomes slow and less efficient in reporting. For this reason, we need a web system for processing population administration data that is able to overcome the problems that are currently happening. The purpose of making this Population Data Processing website is to help provide alternative solutions to problems in Kober village. With this website, it is hoped that population administration services by the Kober Village government to the community can be carried out better, faster and easier